Pendirian Perseroan Terbatas oleh Suami Istri dengan Modal Harta Bersama Beserta Akibat Hukumnya - Widya Elfareda Putri; Hamida Hamida; Sumriyah Sumriyah (International Forum of Researchers and Lecturers, 2024)
A limited liability company (hereinafter referred to as PT) is a capital partnership established under an agreement. This means that in the establishment of a PT there are two or more people in an establishment. In practice there are married couples who establish a joint PT. And in principle, the married couple has joint property after marriage, which means they are considered as one party or one property together. With these circumstances, it is considered not to meet the requirements for the establishment of PT. Law No. 40 of 2007 also does not regulate the exact provisions related to who can become shareholders. For this event, the author is interested in discussing about: (1) What is the validity of a Limited Liability Company established by husband and wife? (2) What are the legal consequences for a limited liability company established by husband and wife? The approach method used in this study is normative juridical, legislative research approach and literature study is carried out by studying literature books and scientific papers related to this issue. The implication is that if the husband and wife do not make a marriage agreement, it will make the husband and wife a subject of law, and be personally responsible for the engagement and losses incurred by the Company and make the liability of the PT unlimited.